Evaluation of sympathetic adrenergic branch of cutaneous neural control throughout thermography and its relationship to nitric oxide levels in patients with fibromyalgia. (January 2021) - Aguilar-Ferrándiz, María Encarnación; Casas-Barragán, Antonio; Tapia-Haro, Rosa Maria; Rus, Alma; Molina, Francisco; Correa-Rodríguez, María
Abstract: Background: Fibromyalgia syndrome is defined as a complex disease, characterized by chronic widespread musculoskeletal pain and other symptoms. The factors underlying physiopathology of fibromyalgia are not well understood, complicating its diagnosis and management. Objectives: To evaluate the peripheral vascular blood flow of the skin of the hands and the core body temperature as indirect measures of sympathetic adrenergic activity of the nervous system and its relationship to nitric oxide levels (NO) in women with fibromyalgia compared with healthy controls. Methods: Forty-two women with fibromyalgia and 52 healthy women were enrolled in this observational pilot study. We used infrared thermography of the hands and an infrared dermal thermometer to evaluate the peripheral vascular blood flow and tympanic and axillary core body temperature, respectively. We measured NO levels using the ozone chemiluminescence-based method. Results: Two-way analysis of covariance (ANCOVA) showed that the tympanic (P=0.002) and hand temperatures were significantly higher in the patients with fibromyalgia than in the controls (P≤0.001). Significant associations were also found between serum NO levels and minimum temperatures at the dorsal center of the dominant hand (β=-3.501; 95% confidence interval [CI] -6.805, ‑0.198; P= 0.038), maximum temperature (β=-5.594; 95% CI ‑10.106, ‑1.081; P=0.016), minimum temperature (β=-4.090; 95% CI ‑7.905, ‑0.275; P=0.036), and mean temperature (β=-5.519; 95% CI ‑9.933, ‑1.106; P=0.015) of the center of the palm of the non-dominant hand, maximum temperature at the thenar eminence of the dominant hand (β=-5.800; 95% CI ‑10.508, ‑1.092; P=0.017), and tympanic temperature (β=-9.321; 95% CI ‑17.974, ‑0.669; P=0.035) in the controls. Conclusions: Our findings indicate that the women with fibromyalgia showed higher tympanic core body and hand temperature than the healthy controls. Moreover, there were negative associations between hand peripheral vasodilation and NO in the healthy women but not in those with fibromyalgia, suggesting a dysfunction of sympathetic cutaneous neural control. Highlights: Women with Fibromyalgia showed higher body core and hands temperature in comparison with healthy controls. Nitric oxide levels may not be associated with body temperature in Fibromyalgia. An impair of the cutaneous sympathetic neural control and thermogenesis in Fibromyalgia patients could explain our results.